Modern scholarship in the study of Torah: contributions and limitations - Carmy, Shalom (The orthodox forum series, 1996)
Challenges the compartmentalization to which we seem all too easily resigned, to discover whether, and to what extent, the methods of modern scholarship can become part and parcel of the study of "Torah", conceived as a religious-intellectual way of life.